Effect of DL-Methionine Supplementation on Tissue and Plasma Antioxidant Status and Concentrations of Oxidation Products of Cholesterol and Phytosterols in Heat-Processed Thigh Muscle of Broilers - Johanna O. Zeitz; Tamara Ehbrecht; Anne Fleischmann; Erika Most; Denise K. Gessner; Silvia Friedrichs; Marion Sparenberg; Klaus Failing; Rose Whelan; Dieter Lütjohann; Klaus Eder (Animals, 2020)
In this study, the hypothesis that supplementation with methionine (Met) as DL-Met (DLM) in excess of the National Research Council (NRC) recommendations improves the antioxidant system in broilers was investigated. Day-old male Cobb-500 broilers (n = 72) were divided into three groups which were fed a control diet or diets supplemented with two levels of DLM in which the concentrations of Met + Cys exceeded the recommendations of NRC by 15–20% (group DLM 1) or 30–40% (group DLM 2), respectively. The three groups of broilers did not show differences in body weight gains, feed intake, and feed conversion ratio. However, broilers of groups DLM 1 and DLM 2 had higher concentrations of glutathione (GSH) in liver and thigh muscle and lower concentrations of cholesterol oxidation products (COPs) in heat-processed thigh muscle than broilers of the control group. Concentrations of several oxidation products of phytosterols in heat-processed thigh muscle were also reduced in groups DLM 1 and DLM 2; however, the concentration of total oxidation products of phytosterols was not different between the three groups. The study shows that DLM supplementation improved the antioxidant status due to an increased formation of GSH and reduced the formation of COPs during heat-processing in thigh muscle.